the Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah pada Al-fazza Kredit Syariah Mandiri - Uleng, Ambo; Awaluddin, Awaluddin; Rahman Azis, Abdul (IRPI Publisher, 2023)
This study aims to determine the effect of physical evidence, reliability, responsiveness, assurance and empathy on customer satisfaction at Al-Fazza Kredit Syariah Makassar. The type of research used in this research is quantitative with an explanatory research approach. The analysis in this study is multiple linear analysis. In this study, some of the employees of Al-Fazza Kredit Syariah were sampled. To determine the number of samples in this study, a simple random sampling technique was used. The sampling technique uses the slovin formula so that 65 respondents are obtained. Data collection techniques using questionnaire techniques. The data analysis technique uses multiple linear regression tests. The results of the study show that physical evidence, reliability, responsiveness, assurance and empathy have an effect on customer satisfaction at Al-Fazza Makassar Syariah Credit.